Formation and management of the enterprise's image as a factor of competitiveness - Tur, Olesya; Tur, Oleksandr (My University, 2020)
The formation of the enterprise's image at each stage of enterprise development was studied and it was found out that this is a long and cost-effective process that requires consistency, but comparing costs and effects justifies actions. It was also determined that the formation of the enterprise's image occurs under the influence of external necessity, which arises in a competitive environment and is aimed at both external and internal target audiences. To enhance the influence of the emotional component of the image, the enterprise forms not only a positive image through the results of its activities, but also such external indicators as location, interior, appearance of personnel, management. Also, an important condition for creating a positive image is the establishment of public relations, mass media, and constant identification of the nature of perception of the company's image by various groups of the population when conducting sociological research. In the course of the research, tools for forming a positive image of the enterprise were identified, such as positioning, manipulation, mythologization, emotionalization and visualization. It was revealed that the image of an enterprise consists of the following structure: the image of the product, the image of the consumer of the product, the internal image of the enterprise, the image of the leader, the visual image of the enterprise, the social image of the enterprise. It was found out that after forming the image of an enterprise, it is necessary to manage it on the basis of periodic assessment of it. Therefore, image management can be carried out both at the level of a special public relations department and at the level of enterprise management. As for the periodic assessment of the enterprise's image, it can be carried out by full-time specialists who know the basics of improving the image or involve specialists from specialized agencies. During the study, qualitative models for assessing the image of an enterprise were identified, namely: a constructive model, a ranking method, focus groups that are focused on identifying deep and unconscious characteristics of people's consciousness and quantitative models (questionnaires, interviews). There are also methods for assessing the image of an enterprise using: semantic differential, scales, integral indicators, etc. They allow you to consider from different angles the effectiveness of image influence on the profitability of an organization and its economic indicators. There is also an analysis of secondary information to assess the image: content and intent analysis is the consideration of exactly those sources of information that the company uses to influence its contact audiences. The more widely an enterprise collects information from various informants, the more complete picture of its image in current market situation is created. And the formation of the image was studied on the example of ALC "Yagotynsky Butter Plant" and it was found out that this enterprise has a high competitiveness, since it produces high-quality products, helps the environment and society by holding various events and actions. Досліджено формування іміджу підприємства на кожному етапі розвитку підприємства та з’ясовано, що це тривалий і економічно ефективний процес, який вимагає послідовності, але порівняння витрат і ефекту виправдовує дії. Також визначено, що формування іміджу підприємства відбувається під впливом зовнішньої необхідності, яка виникає в конкурентному середовищі та спрямована як на зовнішню, так і на внутрішню цільову аудиторію. Для посилення впливу емоційної складової іміджу підприємство формує не тільки позитивний імідж за результатами своєї діяльності, а й за такими зовнішніми показниками, як розташування, інтер'єр, зовнішній вигляд персоналу, керівництво. Також важливою умовою створення позитивного іміджу є налагодження зв'язків з громадськістю, ЗМІ, постійне виявлення характеру сприйняття іміджу компанії різними групами населення при проведенні соціологічних досліджень. У ході дослідження були виявлені такі інструменти формування позитивного іміджу підприємства, як позиціонування, маніпулювання, міфологізація, емоціоналізація та візуалізація. Виявлено, що імідж підприємства складається з такої структури: імідж товару, імідж споживача товару, внутрішній імідж підприємства, імідж керівника, візуальний імідж підприємства, імідж підприємства. соціальний імідж підприємства. З’ясовано, що після формування іміджу підприємства необхідно керувати ним на основі періодичної його оцінки. Тому управління іміджем може здійснюватися як на рівні спеціального відділу зв'язків з громадськістю, так і на рівні керівництва підприємства. Що стосується періодичної оцінки іміджу підприємства, то її можуть проводити штатні спеціалісти, які знають основи підвищення іміджу, або залучати фахівців спеціалізованих установ. У ході дослідження були виділені якісні моделі оцінки іміджу підприємства, а саме: конструктивна модель, метод ранжування, фокус-групи, які орієнтовані на виявлення глибинних і неусвідомлюваних характеристик свідомості людей та кількісні моделі (анкетування, інтерв’ю). Існують також методи оцінки іміджу підприємства за допомогою: семантичного диференціалу, шкал, інтегральних показників тощо. Вони дозволяють з різних боків розглянути ефективність впливу іміджу на прибутковість організації та її економічні показники. Також існує аналіз вторинної інформації для оцінки іміджу: аналіз вмісту та намірів — це врахування саме тих джерел інформації, які компанія використовує для впливу на свою контактну аудиторію. Чим ширше підприємство збирає інформацію від різноманітних інформаторів, тим повніше створюється картина його іміджу в поточній ринковій ситуації. А формування іміджу досліджено на прикладі ТзОВ «Яготинський маслозавод» та з’ясовано, що це підприємство має високу конкурентоспроможність, оскільки виробляє якісну продукцію, допомагає довкіллю та суспільству шляхом проведення різноманітних заходів та акцій.
Keywords: кафедра економіки праці та менеджменту; image of the enterprise; competitiveness; image assessment; імідж підприємства; конкурентоспроможність; оцінка іміджу